(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A circular Defected Ground Structure is proposed to improve the radiation properties of a Rectangular Microstrip Patch Antenna with Quarter Wave Transformer feed (QWTRMPA). By crack down cross-polarization (XP) levels, higher isolation between co-polarization to cross-polarization radiation is achieved without disturbing the co-polarized radiation. In this design a circular slot etched on the ground plane as a Defected Ground Structure (DGS) results in a suppression of XP in H-plane. The conventional configuration resonates at 5.24 GHz, having a co-polarization peak gain of 4.5 dB and total isolation of 27 db. The proposed MPA shows compactness of 420 MHz by resonating at 4.82 GHz with total isolation of 44 db. The XP levels fall below 17 dB in H-plane when compared to the conventional configuration. The fabrications of proposed and conventional prototypes are done using the substrate FR4 epoxy whose dielectric constant is 4.4 and thickness of 1.6 mm. The simulation results go hand in hand with the experimental data.